Ovarian Adult Granulosa Cell Tumor – a rare case report - Joshi, Rijuta; Baral, Gehanath; Malla, Karishma (Nepal Journal of Obstetrics and Gynaecology, 2018)
Introduction: Adult granulosa cell tumor is a rare tumor which accounts for 1% of all ovarian tumors. They usually present with postmenopausal bleeding and abdominal mass. Inhibin is used as the tumor marker. Case: A 76 years multiparous post-menopausal women presented with vaginal bleeding for past three years and painless huge mass in lower abdomen. She underwent total abdominal hysterectomy with bilateral salphingo-oophorectomy with bilateral pelvic lymphnode dissection with appendectomy. Histopathology showed the adult granulosa cell tumor with few mitosis, Stage IA. Her postoperative period was uneventful. Conclusion: Surgery is the mainstay of treatment of granulosa cell tumor and chemotherapy is indicated in advanced cases. Although they have better prognosis, life-long follow up is advised to detect late recurrence.